Social impact analysis on environmental conflict dynamics at coal fired steam power plant - Ria Ishardanti (Institute for Advanced Science Social, and Sustainable Future, 2023)
This article examines the dynamics of environmental conflict to the community around the Batang Coal Fired Steam Power Plant as a case study. Rejection of it appears in the early stage of the construction because of its thread to the environment and economic resources, mostly to farmers and fishers. Batang Coal Fired Steam Power Plant has track records of conflict turmoil from behalf of the Ujungnegoro, Kandeman District, Central Java. This study used a qualitative approach with in-depth interviews and FGD methods to affected districts and related government agencies, as well as analyzing environmental pollution. Social impact assessments (SIA) are a framework to investigate the causes, dynamics, and resolution of social-environmental conflicts. This study found out that the root cause of environmental conflict starts with ecological degradation. The dynamics of social and economic will accumulate until a form of conflict. This study offers conflict management models in resolving social-environmental conflict.